Historical Evolution of Second-Line Therapy in Non-Small Cell Lung Cancer - Lazzari, Chiara; Bulotta, Alessandra; Ducceschi, Monika; Viganò, Maria Grazia; Brioschi, Elena; Corti, Francesca; Gianni, Luca; Gregorc, Vanesa (Frontiers in Medicine, 2017)
Innovative therapeutic agents have significantly improved outcome with an acceptable safety profile in a substantial proportion of non-small cell lung cancer (NSCLC) patients, who depend on oncogenic molecular alterations for their malignant phenotype. Despite the survival improvement achieved with first-line chemotherapy, about 30% of patients do not obtain a tumor response. Moreover, those patients, initially sensitive to treatment, acquire resistance and develop tumor progression after a median of about 5 months. Approximately 60% of the patients progressing from first-line chemotherapy receive further systemic treatment in the second-line setting. Moreover, new options have emerged in the second-line armamentarium for the treatment of patients with NSCLC, including immune checkpoint inhibitors and antiangiogenic agents. The current review provides an overview on the clinical studies that gained the approval of chemotherapy agents (docetaxel and pemetrexed) and epidermal growth factor receptor gene–tyrosine kinase inhibitors as second-line treatment options for NSCLC patients, not carrying molecular alterations.